MANAGEMENT OF OF OESTROUS CYCLE IN CROSSBRED COWS USING PROSTAGLANDIN - G. Ajitkumar (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
Trials carried out to study the efficacy of prostaglandin in the management of oestrous cycle in crossbred cows revealed that PGF, alpha could Ix: successfully used for induction of oestrus in crossbred cows with fixed time insemination. However, comparative studies on fertility in relation to insemination at detected oestrus and at fixed time after administration of PGF, alpha are warranted.